2018
DOI: 10.1051/swsc/2018023
|View full text |Cite
|
Sign up to set email alerts
|

Predicting well-connected SEP events from observations of solar soft X-rays and near-relativistic electrons

Abstract: -This paper studies the use of electron data from the Electron Proton Alpha Monitor (EPAM) on board the Advanced Composition Explorer (ACE) in the UMASEP (University of Málaga Solar particle Event Predictor) scheme [Núñez, Space Weather 9 (2011) S07003; Núñez, Space Weather 13 (2015)] for predicting well-connected >10 MeV Solar Energetic Proton (SEP) events. In this study, the identification of magnetic connection to a solar particle source is done by correlating Geostationary Operational Environmental Satelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…Further, Michalek (2009) showed a good correlation between the energy of the CME and the peak of the X-ray flare. Finally, recent studies showed that the X-ray flux ratio is a good predictor for extreme solar events (Núñez, 2018;Kahler and Ling, 2018).…”
Section: Model Features and Data Sourcesmentioning
confidence: 98%
See 1 more Smart Citation
“…Further, Michalek (2009) showed a good correlation between the energy of the CME and the peak of the X-ray flare. Finally, recent studies showed that the X-ray flux ratio is a good predictor for extreme solar events (Núñez, 2018;Kahler and Ling, 2018).…”
Section: Model Features and Data Sourcesmentioning
confidence: 98%
“…To assess the viability of moving beyond solar wind-driven models using operationally-available data, we also investigate the inclusion of solar X-ray flux data as a model parameter. Solar Xray flux was chosen as recent studies have shown that these data can be used to forecast solar flare activity (Winter and Balasubramaniam, 2015) as well as Solar Energetic Particle (SEP) events (Núñez, 2018). While the majority of large geomagnetic storms are caused by CMEs (e.g., Gonzalez et al, 1999), it has been shown that CMEs are correlated with solar flare activity (Zhou et al, 2003;Kay et al, 2003;Wu et al, 2008;Lippiello et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The US National Weather Service uses this measure to assess predictors because, according to them [37], it is an unbiased verification statistic appropriate for predicting rare events, and, for this reason, it is used to assess severe weather predictors. CSI has also been used in SEP event prediction modeling for optimizing POD and FAR [38][39][40]. The CSI combines POD and FAR as follows: CSI = (POD −1 + (1 − FAR) −1 − 1) −1 .…”
Section: Optimization Of the Decision Treementioning
confidence: 99%
“…Regarding solar EM data, this scheme has been used with SXR flux (Núñez, 2011(Núñez, , 2015Núñez et al, 2017), and microwave (MW) flux density at 5 and 9 GHz (Zucca et al, 2017). Regarding in-situ particle data, this scheme has been used with differential proton fluxes; recently, it has also been used with relativistic electron data (Núñez, 2018).…”
Section: The Modelmentioning
confidence: 99%
“…In this paper we study the use of EUV observations in the UMASEP scheme and analyze the possibility of using them in real-time operations. The UMASEP scheme has been used to develop several real-time prediction tools: UMASEP-10 (Núñez, 2011), UMASEP-100 (Núñez, 2015) and HESPERIA UMASEP-500 (Núñez et al, 2017;Núñez, 2018) which predict >10 MeV, >100 MeV and >500 MeV SEP events, respectively. Since 2010, the UMASEP-10's forecasts are disseminated by NASA's integrated Space Weather Analysis system (iSWA), and the model has shown promise on an operational level (Tsagouri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%